Analysis of the concentration of heavy metals and their vehicle emission in urban road dust of Kathmandu valley - Bikram Kumar Das; Ram Kumar Sharma; Madhav Narayan Shrestha; Basant Lekhak (Journal of Innovations in Engineering Education, 2024)
Greater environmental harm and health risks are associated with fine urban dust than with coarser urban dust. This study aims to analyze the heavy metal (Cu, Zn and Cd) concentration of heavy traffic road sections and compares it with medium traffic road sections with the same starting and end point for a study of how heavy metals from vehicles contribute to road dust (size <150µm). Twenty-seven dust samples of spatial and temporal vary were collected from the study area and were analyzed by Atomic Absorption Spectrophotometer with acetylene flame for zinc, copper, and Cadmium. Cadmium is not detected (<0.5 mg/kg) in any of the samples. The decreasing order of average concentration of zinc and copper in street dust is found from high traffic road to medium traffic roads and Low traffic roads. The ANOVA combined with IBM SPSS statistics software results at a significance level (α = 0.05) suggest that the mean average concentration of Zinc (Zn) of different road groups classified are significantly different (F3.402 = 5.75 and p < (α = 0.05)). The ANOVA results at the significance level (α = 0.05) of Copper (Cu) of the three road groups classified are not found to be significantly different (F3.402 = 2.446 and p > (α = 0.05)). Therefore it can be said that vehicle volume effect directly on the contribution of zinc in roadside dust but the Copper concentration seems to be influenced by some other contributors like construction activities, burning of coal.